COMPARISON BETWEEN WING LOADING AND ASPECT RATIO FOR FRUIT BATS (FAMILY PTEROPODIDAE) AND ROUNDLEAF BATS (FAMILY HIPPOSIDERIDAE) - Ilya Natasya, Yakcop (Universiti Malaysia Sarawak, (UNIMAS), 2017)
This thesis study was conducted as an attempt to compare between the wing loading and aspect ratio of fruit bats (Family Pteropodidae) and roundleaf (Family fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference Hipposideridae) bats to describe the habitat preference of both fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference families using secondary data from previous studies. Based on the wing tracing and calculation of flight morphology of bats, classification of bats were based on high, medium, and low wing loading and aspect ratio. The study shows that fruit bats have relatively high wing loading and aspect ratio whereas roundleaf bats have low wing loading and aspect ratio. Bats with higher wing loading and aspect ratio were commonly occupy habitat with less cluttered while bats with lower wing loading and aspect ratio were commonly occupy cluttered habitat. There are high degrees of species overlap between the two families of bats in which they occupies the fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference same habitat. This might increase the competition on roosting area as well as foraging behavior between species. fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference Wing loading and aspect ratio is used to explain the flight behavior, flight performance, and habitat preferences fruit bats, roundleaf bats, wing loading, aspect ratio, habitat preference for both families.